EFFECT OF FOLIAR APPLICATION OF ORGANIC EXTRACT AND HAMIC ACID APPLICATION ON STRAWBERY PRODACTION - & Al-Rawi, AL- Karawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out in greenhouse Date to palm Research units, College of Agriculture, University of Baghdad ( Abu Ghraib ) , seasons 2013 and 2014 to investigate the effect of foliar application organic matter extract and humic acid and their interactions on yield of strawberry plants . The study include 12 treatments , to spray strawberry’s plant with four levels of organic matter spray included distilled water only (T0) , (1) volume of organic matter extract to volume of distilled water ( 1:1) (T1) , (2) volume of organic matter extract to volume of distilled water (2:1 ) (T2 ) and (3) volume of organic matter extract volume of distilled water (3:1) (T3), the second factor was three concentrations of humifert-ultra , 0( H0 ) , 2.5 ml.L-1 ( H2.5) and 5 ml.L-1 ( H5 ) to the soil . Factorial Experiment carried out according to RCBD with three replications , averages compared by LSD test at the level of 5% probability. Results that have been obtained is that spraying plants extract organic matter led to a significant increase in the number of flowers and the percentage of the contract and the number of fruits and had no significant effect on yield of plant. addition of humic acid led to a significant increase in the number of flowers and the percentage of fruit set and the number of fruits and fruit weight and yield of plant .